AKASI and Near-Infrared Spectroscopy in the combined effectiveness evaluation of an actinic keratoses preventive product in immunocompetent and immunocompromised patients - Veronese, Federica; Seoni, Silvia; Tarantino, Vanessa; Buttafava, Matteo; Airoldi, Chiara; Meiburger, Kristen M.; Zavattaro, Elisa; Savoia, Paola (Frontiers in Medicine, 2022)
Introduction The high incidence of actinic keratoses among both the elderly population and immunocompromised subjects and the considerable risk of progression from in situ to invasive neoplasms makes it essential to identify new prevention, treatment, and monitoring strategies. Objective The aim of this study was to evaluate the efficacy on AKs of a topical product (®Rilastil AK Repair 100 +) containing high-protection sunscreens, a DNA Repair Complex with antioxidant and repairing action against UV-induced DNA damage, and nicotinamide, a water-soluble derivative of vitamin B3 that demonstrated several photoprotective effects both in vitro and in vivo. Methods The study enrolled 74 Caucasian patients, which included 42 immunocompetent and 32 immunosuppressed subjects. The efficacy of the treatment has been evaluated through the clinical index AKASI score and the non-invasive Near-Infrared Spectroscopy method. Results The AKASI score proved to be a valid tool to verify the efficacy of the product under study, highlighting an average percentage reduction at the end of treatment of 31.37% in immunocompetent patients and 22.76% in organ transplant recipients, in comparison to the initial values, with a statistically significant reduction also in the single time intervals (T0 vs. T1 and T1 vs. T2) in both groups. On the contrary, the Near-Infrared Spectroscopy (a non-invasive technique that evaluates hemoglobin relative concentration variations) did not find significant differences for O2Hb and HHb signals before and after the treatment, probably because the active ingredients of the product under study can repair the photo-induced cell damage, but do not significantly modify the vascularization of the treated areas. Conclusion The results deriving from this study demonstrate the efficacy of the product under study, confirming the usefulness of the AKASI score in monitoring treated patients. Near-Infrared Spectroscopy could represent an interesting strategy for AK patients monitoring, even if further large-scale studies will be needed.